Pelaksanaan Penolakan Perkawinan Usia Dini di KUA Kecamatan Modo dalam Prespektif Undang-Undang Nomor 1 Tahun 1974 dan 16 Tahun 2019 - Naysha Nur Azizah; Eko Wahyudi (Transbahasa, 2026)
Early-age marriage remains one of the legal issues encountered in the implementation of the minimum age requirement for marriage as stipulated in Law Number 16 of 2019 concerning the amendment to Law Number 1 of 1974 on Marriage. This study aims to examine the implementation of the rehection of early age marriage at the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Modo District, Lamongan Regegency, as well as the obstacles affecting its implementation. The research method employed is empirical juridical research, combined with a descriptive qualitative approach. The data were obtained throught interviews, observation, and documentation, and were subsequently analyzed by linking the applicable legal provisions with the empirical conditions found in the field. The resluts of the study indicate that the KUA of Modo District has implemented the rejection of early-age marriage in accordance with the provisions of the prevailing laws and regulations through the examination of administrative reqirements and the issuance of the Marriage Rejection Letter Model N7 for prospective brides and grooms who have not met the minimum age requrement for marriage. The implementation of marriage rehection still faces several obstacles, including the low level of legal awareness among the comunity, inconsistencies in population administration data, and the strong influence of local culture, which continues to tolerate early-age marriage and unregistered marriage. It can be concluded that the implementation of the rejection of early-age marriage at the KUA of Modo Disctrict reflects the application of the principle of legality and legal protection for childern. However, its effectiveness still requires support through the improvement of public legal understanding and the strengthening of thr administration system.